Transmission of Ultrasonic Waves Via Optical Silica Glass Fiber Doped by 7.5% of TiO2 with the Use of Power Sandwich Transducer - MUC, Sylwia; GUDRA, Tadeusz (Archives of Acoustics, 2011)
The possibility of acoustic wave propagation in optical waveguides creates new prospects for simultaneous transmission of laser beams and ultrasonic waves. Combined laser-ultrasonic technology could be useful in e.g. surgical treatment. The article presents the results of experimental studies of transmission of ultrasonic wave in optical fibres, the core of which is doped by 7.5% of TiO2, using a sandwichtype transducer. It also presents amplitude characteristics of an ultrasonic signal propagated in the optical fibre. Authors studied the effect which the length of the fibre has on the achieved output signal amplitudes. They presented the relation of the output signal amplitude from a capacitive sensor to the power applied to the sandwich-type transducer. The obtained results were compared with the results produced when using an optical fibre with a core doped by 3% of GeO2, in order to select optical fibre suitable for simultaneous transmission of ultrasonic waves and laser rays.